The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Hiding in Plain Sight: Elopomorph Larvae Are Important Contributors to Fish Biodiversity in a Low-Latitude Oceanic Ecosystem - Jon A. Moore; Dante B. Fenolio; April B. Cook; Tracey T. Sutton (Frontiers in Marine Science, 2020)

The Vertical and Horizontal Distribution of Deep-Sea Crustaceans in the Order Euphausiacea in the Vicinity of the DeepWater Horizon Oil Spill - Tamara M. Frank; Charles D. Fine; Eric A. Burdett; April B. Cook; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Influence of oceanographic conditions on abundance and distribution of post‐larval and juvenile carangid fishes in the northern Gulf of Mexico - John A. Mohan; Tracey T. Sutton; April B. Cook; Kevin M. Boswell; R. J. David Wells (Fisheries Oceanography, 2017)
Relationships between abundance of post‐larval and juvenile carangid (jacks) fishes and physical oceanographic conditions were examined in the northern Gulf of Mexico (GoM) in 2011 with high freshwater input from the Mississippi River. Generalized additive models ( GAM s) were used to explore complex relationships between carangid abundance and physical oceanographic data of sea surface temperature ( SST ), sea surface height anomaly ( SSHA ) and salinity. The five most abundant carangid species collected were: Selene setapinnis (34%); Caranx crysos (30%); Caranx hippos (10%); Chloroscombrus chrysurus (9%) and Trachurus lathami (8%). Post‐larval carangids (median standard length [ SL ] = 10 mm) were less abundant during the spring and early summer, but more abundant during the late summer and fall, suggesting summer to fall spawning for most species. Juvenile carangid (median SL = 23 mm) abundance also increased between the mid‐summer and early fall. Most species showed increased abundance at lower salinities and higher temperatures, suggesting entrainment of post‐larval fishes or feeding aggregations of juveniles at frontal convergence zones between the expansive river plume and dynamic mesoscale eddy water masses. However, responses were species‐ and life‐stage specific, which may indicate fine‐scale habitat partitioning between species. Ordination methods also revealed higher carangid abundances at lower salinities for both post‐larval and juvenile life stages, with species‐ and life‐stage specific responses to SST and SSHA , further suggesting habitat separation between species. Results indicate strong links between physical oceanographic features and carangid distributions in the dynamic northern GoM.